Medicine's perception of reality – a split picture: critical reflections on apparent anomalies within the biomedical theory of science. Issue 4 (13th May 2015) - Kirkengen, Anna Luise; Ekeland, Tor‐Johan; Getz, Linn; Hetlevik, Irene; Schei, Edvin; Ulvestad, Elling; Vetlesen, Arne Johan
Abstract: Escalating costs, increasing multi‐morbidity, medically unexplained health problems, complex risk, poly‐pharmacy and antibiotic resistance can be regarded as artefacts of the traditional knowledge production in Western medicine, arising from its particular worldview. Our paper presents a historically grounded critical analysis of this view. The materialistic shift of Enlightenment philosophy, separating subjectivity from bodily matter, became normative for modern medicine and yielded astonishing results. The traditional dichotomies of mind/body and subjective/objective are, however, incompatible with modern biological theory. Medical knowledge ignores central tenets of human existence, notably the physiological impact of subjective experience, relationships, history and sociocultural contexts. Biomedicine will not succeed in resolving today's poorly understood health problems by doing 'more of the same'. We must acknowledge that health, sickness and bodily functioning are interwoven with human meaning‐production, fundamentally personal and biographical. This implies that the biomedical framework, although having engendered 'success stories' like the era of antibiotics, needs to be radically revised.